Copy number variation analysis increases the diagnostic yield in muscle diseases. (December 2017) - Välipakka, Salla; Savarese, Marco; Johari, Mridul; Sagath, Lydia; Arumilli, Meharji; Kiiski, Kirsi; Sáenz, Amets; de Munain, Adolfo Lopez; Cobo, Ana-Maria; Pelin, Katarina; Udd, Bjarne; Hackman, Peter
Abstract : Objective: Copy number variants (CNVs) were analyzed from next-generation sequencing data, with the aim of improving diagnostic yield in skeletal muscle disorder cases. Methods: Four publicly available bioinformatic analytic tools were used to analyze CNVs from sequencing data from patients with muscle diseases. The patients were previously analyzed with a targeted gene panel for single nucleotide variants and small insertions and deletions, without achieving final diagnosis. Variants detected by multiple CNV analysis tools were verified with either array comparative genomic hybridization or PCR. The clinical significance of the verified CNVs was interpreted, considering previously identified variants, segregation studies, and clinical information of the patient cases. Results: Combining analysis of all different mutation types enabled integration of results and identified the final cause of the disease in 9 myopathy cases. Complex effects like compound heterozygosity of different mutation types and compound disease arising from variants of different genes were unraveled. We identified the first large intragenic deletion of the titin ( TTN ) gene implicated in the pathogenesis of a severe form of myopathy. Our work also revealed a "double-trouble" effect in a patient carrying a single heterozygous insertion/deletion mutation in the TTN gene and a Becker muscular dystrophy causing deletion in the dystrophin gene. Conclusions: Causative CNVs were identified proving that analysis of CNVs is essential for increasing the diagnostic yield in muscle diseases. Complex severe muscular dystrophy phenotypes can be the result of different mutation types but also of the compound effect of 2 different genetic diseases.